Me and My VE, Part 3. (September 2014) - Strater, Laura; Kennedy, Rebecca A.; Scerbo, Mark W.; Papelis, Yiannis; Croll, Menion; Garcia, Hector; Griffith, Tami; Flynn, Jeremy R.; Proaps, Alexandra B.; Shah, Smruti J.; Procci, Katelyn; Bowers, Clint
With the constant push to do more for less, the use of virtual environments (VE), simulations and serious games has exploded. Human Factors (HF) personnel often use these tools to support a range of activities, including modeling process or the effects of humans in the system; designing, testing and validating new systems and processes; training skills, procedures and techniques; and even for therapeutic activities. This session will describe and demonstrate some of the diverse uses for virtual environments (VEs) in an alternate demonstration format. The session will begin with demonstrators providing a brief description of their VE, and how they've used it to answer a critical research question or address a unique need, including a video demonstration of the VE in action. After these introductions, all demonstrations will be set up around the room, and session attendees can move around the room for direct interaction with the demonstrations. This session should provoke ideas among attendees for how VEs, simulations and serious games can help address their research, training, education, evaluation or therapeutic needs.